Faktor-Faktor yang Mempengaruhi Pengelolaan Dana Desa di Gorontalo - Usman Usman; Mahfiza Mahfiza; Merci Lamusi (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2022)
The present research aimed to figure out to what extent the effect of accountability on village fund management, the effect of transparency on village fund management, and the simultaneous effect of accountability and transparency on village fund management in Duhiadaa Subdistrict, Pohuwato Regency. It employed quantitative research using primary data obtained from distributing questionnaires to village apparatus in Duhiadaa Subdistrict, Pohuwato Regency. In the meantime, the data analysis technique research used a validity test, reliability test, classical assumption test, and multiple linear regression tests using SPSS. The research finding depicted that accountability and transparency had a positive and significant effect on village fund management in Duhiadaa Subdistrict, Pohuwato Regency. The coefficient of determination obtained was 32.3%, which meant that accountability and transparency could explain the village fund management in Duhiadaa Subdistrict, Pohuwato Regency of 32.3%. In comparison, the remaining could be explained by other variables that were not included in this research